Fungal community dynamics during degradation of poly(butylene succinate-co-adipate) film in two cultivated soils in Japan. Issue 5 (3rd May 2020) - Yamamoto-Tamura, Kimiko; Hoshino, Yuko Takada; Tsuboi, Shun; Huang, Chuan; Kishimoto-Mo, Ayaka Wenhong; Sameshima-Yamashita, Yuka; Kitamoto, Hiroko
ABSTRACT: Fungi play an important role in the degradation of biodegradable plastics (BPs) in soil. However, little is known about their dynamics in the soil during the degradation of BPs. We studied the community dynamics of BP-degrading fungi during poly(butylene succinate -co- adipate) (PBSA) film degradation in two different types of soils using culture-dependent and culture-independent methods. The Fluvisol and the Andosol soils degrade embedded PBSA films at high and low speeds, respectively. The number of PBSA emulsion-degrading fungi that increased in the Fluvisol soil was higher than that in the Andosol soil after embedding with PBSA films. We succeeded in detecting internal transcribed spacer 1 (ITS1) regions those matched that of the fungi by polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) in both soils. Our results suggest that fungal community analyses using PCR-DGGE in combination with BP degraders isolation techniques enables the monitoring of BP films-degrading fungi. GRAPHICAL ABSTRACT: uf0001 Monitoring fungal population dynamics during the degradation of films comprising poly(butylene succinate- co -adipate) in a Fluvisol and an Andosol soil.